Investigação de bactérias patogênicas por técnicas moleculares em um sistema de tratamento de esgotos composto por reator UASB e lagoas de polimento - Valeria Martins Godinho (2010)
The present work aimed to investigate pathogenic bacteria in a wastewater treatment system composed by one UASB reactor and three polishing ponds in series using PCR technique and FISH techniques. A comparison between the Colilert® and FISH techniques to quantify E.coli was also done. Environmental conditions on the ponds were evaluated through monitoring of physical and chemical parameters, in order to verify their possible influence on the occurrence and decay of the pathogenic bacteria. The research was developed in a pilot treatment plant (200 population equivalents) treating urban wastewater from the city of Belo Horizonte/Brazil. Four sampling campaigns were undertaken to investigate bacteria by PCR and subsequent quantification using FISH technique. To compare Colilert® and FISH techniques for the quantification of E. coli, six sampling campaigns were done. Monitoring ofphysical and chemical parameters was carried out from December/2006 until March/2009. Regarding the investigation of the occurrence of pathogenic bacteria using PCR, there were positive results for E. coli, Salmonella spp. (only in ponds 1 and/or 3), Enterococcus spp. andCampylobacter jejuni. Salmonella Typhimurium, Shigella spp. and Shigella dysenteriae were detected only at the initial stages of the system (raw wastewater and/or UASB and/or pond 1). The species H. pylori, S. aureus and Y. enterocolitica were not detected in any of the four samples collected. Regarding quantification of bacteria by FISH the following mean values were found in the raw wastewater, pond 1 effluent and pond 3 effluent, respectively (values in cells per 100 ml): E. coli 2.3x107, 4.8x106 and 4.5x106; Salmonella 8.6x106, 3.4x106 and 5.4x106; Campylobacter spp. 4.5x106, 6.1x105 and 7.3x105; Enterococcus 1.6x106, 2.6x105and 1.3x105. When comparing Colilert® and FISH for E. coli quantification, the results obtained were, respectively: raw wastewater 1.1x108 MPN/100ml and 4.0x107 cells/100ml; pond 1 effluent 5.5x105 MPN/100ml and 3.8x106 cells/100ml; pond 3 effluent 5.2x103 MPN/100ml and 3.1x106 cells/100ml. Regarding the influence of environmental conditions in the ponds, no single factor alone showed to be responsible for the decay of the pathogenic organisms in the ponds, and it is likely that their simultaneous interaction was the dominant factor. However, temperature, dissolved oxygen and pH seemed to be the most influentialfactors.